Lupkriuk: usaha cemilan kecil yang menghasilkan manfaat besar - Sabrina, Diha Rifa; Puspitasari, Novi Dwi; Masfufah, Asyiqotul (Maliki Interdisciplinary Journal, 2025)
In the midst of intense business competition in this modern era, product innovation is the key to competitive advantage. This research examines the LupKriuk business, an innovative dried spring roll snack with a four-month shelf life and various flavors, in response to the market's need for practical snacks. This article outlines the various benefits that Lupkriuk has generated. Firstly, the creativity benefits can be seen in the attractive marketing and branding strategies, sustainable product innovation and operational efficiency. Secondly, social benefits include community economic empowerment through job creation, development of entrepreneurial spirit, community strengthening and increased awareness of education. Finally, the personal benefits for business actors are the development of technical and managerial skills, increased creativity, additional income opportunities, expanding social networks, and satisfaction and sense of achievement.